Consistency of voter lists in Bangladesh 1973-2001: an analysis of macro and micro evidence - Eshrat, Monoara (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Governance and Development, 2006.